Long Non-Coding RNAs in Cryptococcus neoformans: Insights Into Fungal Pathogenesis - Kalem, Murat C.; Panepinto, John C. (Frontiers in Cellular and Infection Microbiology, 2022)
Long non-coding RNAs (lncRNAs) are highly expressed and can modulate multiple cellular processes including transcription, splicing, translation, and many diverse signaling events. LncRNAs can act as sponges for miRNAs, RNA and DNA binding proteins, functioning as competitive endogenous RNAs. The contribution of lncRNAs to microbial pathogenesis is largely neglected in eukaryotic pathogens despite the abundance of RNA sequencing datasets encompassing conditions of stress, gene deletions and conditions that mimic the host environment. The human fungal pathogen Cryptococcus neoformans encodes 6975 (84%) protein-coding and 1359 (16%) non-protein-coding RNAs, of which 1182 (14.2%) are lncRNAs defined by a threshold of greater than 200 nucleotides in length. Here, we discuss the current state of knowledge in C. neoformans lncRNA biology. Utilizing existing RNA seq datasets, we examine trends in lncRNA expression and discuss potential implications for pathogenesis.